Analisis Kreativitas Siswa dalam Pembelajaran Seni Rupa Anyaman Kain Flanel - Ridho, Muhammad Ainur; Oktavia, Devi; Prameisthi, Denna Aji; Astuti, Devina Dwi (CV. ITTC INDONESIA, 2024)
This research was conducted at SD Negeri 3 Karangampel on grade V students. This research was conducted with the aim of knowing the creativity of grade V students at SD Negeri 3 Karangampel in learning fine arts through weaving activities using flannel fabric. This study used a narrative qualitative research approach. Data collection in this study applies triangulation techniques, which combine three different approaches to ensure the accuracy and validity of information, namely observation, interviews, and documentation. The subjects in this study were all grade V students of SD Negeri 3 Karangampel totaling 8 students. The results of this study prove that most students at SD Negeri 3 Karangampel have illustrated extraordinary creativity in learning fine arts through flannel weaving artwork. However, a small number of students still need additional encouragement to bring out their creativity in weaving art using flannel, this is motivated by some students who still feel afraid to try new things.